TEDHAK SITEN: AKULTURASI BUDAYA ISLAM- JAWA (STUDI KASUS DI DESA KEDAWUNG, KECAMATAN PEJAGOAN, KABUPATEN KEBUMEN) - Nuryah Nuryah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
This paper describes About Tedhak Siten as acculturation Islam - Java. The article describes a study initiated Of A Village kedawung, District Pejagoan, Kebumen, Central Java, then society in kedawung Village, District Pejagoan classified as Java community. Properly on Java community in general, society in kedawung Village, District Pejagoan Also running religious rituals in traditional Javanese, although some rituals Performed By community in the village kedawung. People in the village kedawung, District Pejagoan hearts run Tedhak Siten Tradition now has much different from rules indigenous people of Java. Had a lot of 'people in the village Kedawung, District Pejagoan implement Tedhak Siten with more how well as shape the practical and modern. Tedhak Siten what do usually kids time 7 months old Javanese calendar And first down through the soil. Singer it is customary or habits that are very good For Ask The Java community Condensed spiritual with not contradict the norms of Islam. So we must be proud and maintain the preservation of the culture.